Endogenous CCL21-Ser deficiency reduces B16–F10 melanoma growth by enhanced antitumor immunity - Ryonosuke Fujie; Kaoru Kurowarabe; Yuki Yamada; Kakeru Fujiwara; Hayato Nakatani; Kenta Tsutsumi; Ryota Hayashi; Hinami Kawahata; Megumi Miyamoto; Madoka Ozawa; Tomoya Katakai; Yousuke Takahama; et al. (Heliyon, 2023)
The chemokine CCL21 regulates immune and cancer cell migration through its receptor CCR7. The Ccl21a gene encodes the isoform CCL21-Ser, predominantly expressed in the thymic medulla and the secondary lymphoid tissues. This study examined the roles of CCL21-Ser in the antitumor immune response in Ccl21a-knockout (KO) mice. The Ccl21a-KO mice showed significantly decreased growth of B16–F10 and YUMM1.7 melanomas and increased growth of MC38 colon cancer, despite no significant difference in LLC lung cancer and EO771 breast cancer. The B16–F10 tumor in Ccl21a-KO mice showed melanoma-specific activated CD8+ T cell and NK cell infiltration and higher Treg counts than wild-type mice. B16–F10 tumors in Ccl21a-KO mice showed a reduction in the positive correlation between the ratio of regulatory T cells (Tregs) to activated CD8+ T cells and tumor weight. In Ccl21a-KO tumor, the intratumoral Tregs showed lower co-inhibitory receptors TIM-3 and TIGIT. Taken together, these results suggest that endogenous CCL21-Ser supports melanoma growth in vivo by maintaining Treg function and suppressing antitumor immunity by CD8+ T cells.